Complications of transcatheter closure of atrial septal defects. Issue 12 (23rd August 2005) - Spence, M S; Qureshi, S A
Abstract : Transcatheter device closure of atrial septal defects has proved to be remarkably successful, and is usually preferred by both patients and parents. But how does it compare with the gold standard of surgical closure?